Pendidikan Islam Moderat dalam Perspektif Multi situs:: Studi Kasus di Pondok Pesantren Mambaul Falah Dan Pondok Pesantren Mambaus Sholihin 2 Blitar - Chilyatul Mifroha; Mohammad Rofiq (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study purpose to: (1) identify the classical Islamic texts (kitab kuning) taught at Pondok Pesantren Mambaul Falah and Pondok Pesantren Mambaus Sholihin 2 in Blitar; (2) analyze the process of moderate Islamic education implemented at both pesantren; and (3) identify the similarities and differences between the two institutions. A qualitative descriptive approach was used, with data collected through in-depth interviews with administrators, teachers (ustadz), and students (santri) from both pesantren. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that both pesantren share common strategies in promoting moderate Islamic values through the curriculum of classical Islamic texts and student-centered activities. The kitab kuning are applied contextually to instill values of moderation, tolerance, and Islam as a mercy to all (rahmatan lil 'alamin). The educational process includes kitab kuning reading sessions (mathla’ah), problem-solving discussions (bahtsul masa’il), critical reflection on classical scholars (i’tibar), and daily poetry programs. The internalization of moderate Islamic values is also carried out through humanistic approaches, the use of culture as a unifying medium, and the actualization of Islamic teachings in harmony with national values. While both pesantren employ similar frameworks, each has distinct methods and emphasis in delivering their educational goals. This study highlights the important role of pesantren in shaping moderate Islamic thought within Indonesian society.